Research Study Reveals Factors That Impacted Ohio Funeral Director Attrition and Retention Rates - Tyler J. O’Brien (Journal of Death, 2025)
A phenomenological qualitative study was conducted to obtain facts and details about the lived experiences of Ohio funeral directors during their first five years of licensure. The goal of the study was to understand these lived experiences as told by funeral directors to understand better the factors that impact the attrition and retention of new licensees. The data was analyzed using the Colaizzi 1978 method. The collected data aided in professional development programs offered to Ohio funeral directors and embalmers which increased the discussion and interest in factors that impact attrition and retention rates of new funeral director licensees at the local and national levels. The information from the study can be applied to allied helping professions such as healthcare, ministerial, and education. The stories and experiences as told by Ohio funeral directors provides new insight into the factors that impact attrition and retention rates of new licensees.
Keywords: Funeral Director